Dual-phase nanostructuring of layered metal oxides for high-performance aqueous rechargeable potassium ion microbatteries - Ying-Qi Li (Nature Portfolio, 2019)
Aqueous rechargeable microbatteries could enable new microelectronics, but their current electrode materials still suffer from low capacity and poor rate capability. Here the authors show that layered K x V2O5·nH2O with an amorphous/crystalline dual-phase nanostructure can address these issues.